Estrés laboral y calidad de atención del personal de salud en el Hospital Básico de Amaluza - Alvarez Merino, Vicenta Maribel (2023)
According to the World Health Organization (WHO), work stress is the reaction of a worker to demands and pressures that do not match his or her knowledge and skills, experiencing his or her ability to cope with the situation. The purpose of this study was to determine the presence of occupational stress and the quality of care provided by the health personnel at Hospital Básico de Amaluza. The universe was made up of 74 health professionals and all the patients who attended for care in the period January-November 2022; it was a quantitative, correlational and cross-sectional study, in which 70 health workers participated, to whom the International Labor Organization (ILO)-(WHO) work stress questionnaire was applied, and 221 citizens who were attended in the health unit, in whom satisfaction with the service provided was evaluated with the CARE-Q instrument (Caring Assessment Instrument). Of the group of participants, 46 women and 24 men were identified, with a predominant age range between 22 and 28 years for both sexes. It was determined that 73.91% of women and 75% of men reported low levels of work stress. On the other hand, it was found that 75.11% of the patients attended by health professionals at Hospital Básico de Amaluza had a high level of satisfaction with the service provided. When relating the variables through the chi-square test, a statistically significant relationship was found with a value of p=0.000, which allowed us to conclude that the quality of patient care is indirectly influenced by the level of occupational stress of the health team